2002
DOI: 10.1097/00024382-200204000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Murine Model of Endotoxin-Induced Acute Lung Injury

Abstract: Endotoxin-induced microvascular lung injury in mice is a commonly used experimental model of the acute respiratory distress syndrome (ARDS). The present paper aimed to characterize this popular model in a comprehensive and systematic fashion. Male C57bl/6 mice (n = 5) were administered an LD55 dose of E. coli endotoxin (15 mg/kg, i.p.), and lungs were harvested at several time points and evaluated for injury as well as for expression of a variety of inflammatory mediators. Endotoxin induced many features chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
88
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(102 citation statements)
references
References 23 publications
12
88
0
2
Order By: Relevance
“…24 h, and was resolving by 48 h. Pulmonary edema as determined by lung wet-to-dry weight ratios was apparent by 2 h, peaked at 6 h, and then gradually declined, but lung water remained elevated even at 48 h. The early and transient alterations in lung function are consistent with the time course of inflammatory cytokine release and pulmonary edema in our studies and as reported in studies of lethal murine endotoxemia (12,18). The fact that the time of maximum edema came 6 h after endotoxin is also identical to the time course of edema in the reported studies of lethal endotoxemia (18).…”
Section: Discussionsupporting
confidence: 90%
“…24 h, and was resolving by 48 h. Pulmonary edema as determined by lung wet-to-dry weight ratios was apparent by 2 h, peaked at 6 h, and then gradually declined, but lung water remained elevated even at 48 h. The early and transient alterations in lung function are consistent with the time course of inflammatory cytokine release and pulmonary edema in our studies and as reported in studies of lethal murine endotoxemia (12,18). The fact that the time of maximum edema came 6 h after endotoxin is also identical to the time course of edema in the reported studies of lethal endotoxemia (18).…”
Section: Discussionsupporting
confidence: 90%
“…3B). This observation is in agreement with a previous report in mice given intraperitoneal endotoxin (31). In addition, lung IL-4 (a Th2 cytokine) levels were significantly enhanced at 24 and 48 h in the LPS-induced ALI mice (Fig.…”
Section: Losartan Inhibits Th1 and Th17 Polarization Responses In Lpssupporting
confidence: 93%
“…The LPS-induced ALI animal model is a common experimental model used for the investigation of molecular mechanisms and drug efficacy in ALI (28). To observe the effect of eriodictyol on ALI, an LPS-induced ALI animal model was therefore established.…”
Section: Resultsmentioning
confidence: 99%